Ultrasensitive Fluorogenic Substrates for Serine Proteases - Butenas, Saulius; DiLorenzo, Maria E; Mann, Kenneth G (Thrombosis and Haemostasis, 1997)
Selective, sensitive assays for the quantitation of serine proteases involved in coagulation and fibrinolysis have been developed employing fluorogenic substrates containing a 6-amino-1-naphthalenesulfonamide leaving group (PNS-substrates). Over one hundred substrates were evaluated for hydrolysis by the serine proteases of blood coagulation and fibrinolysis, and substrate structure-efficiency correlations were examined. PNS-substrates which contain Lys in the P1 position are specific for Lys-plasmin and are either not hydrolyzed or hydrolyzed at a relatively low rate by factor Xa, thrombin, or urokinase-type plasminogen activator (uPA). These substrates allow quantitation of Lys-plasmin at concentrations as low as 1 pM. Eighteen of over 90 substrates tested for factor XIa are hydrolyzed by this enzyme at a relatively high rate reaching a kcat value of 170 s-1 and allowing quantitation of factor XIa at 10 fM. Eighteen of almost 90 PNS-substrates tested display high specificity for thrombin, some exceeding that for factor Xa by > 10,000-fold and > 100-fold for activated protein C (APC). Seven of these substrates have a over 100 s-1 and three of them have a KM below 1 μM. They allow the quantitation of thrombin at concentrations as low as 20 fM. For APC, uPA and the factor Vila/tissue factor complex, quantitation is feasible at 1 pM concentration. For factor Xa and factor VIIa the limits are 0.4 pM and 40 pM respectively. The PNS-substrates presented in this study may be employed for the development of direct and sensitive serine protease assays.